1995
DOI: 10.2527/1995.732472x
|View full text |Cite
|
Sign up to set email alerts
|

Use of plasma urea nitrogen as a rapid response criterion to determine the lysine requirement of pigs2

Abstract: Five experiments were conducted to evaluate the potential use of plasma urea N (PUN) concentrations as a rapid response criterion to determine amino acid requirements. A preliminary experiment (Exp. 1) indicated that a 3-d feeding time was required to re-equilibrate PUN concentrations after a change in the dietary concentration of lysine. In Exp. 2, 3, and 4, PUN was used to estimate the lysine requirement of growing pigs at different specific BW. Thirty individually penned crossbred pigs weighing 32 and 44 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
129
4
10

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(157 citation statements)
references
References 0 publications
14
129
4
10
Order By: Relevance
“…PUN generally shows a high variance (Coma et al, 1995) and in some studies, PUN was not efficient to determine the lysine requirement (Fontes et al,.1999;Gasparotto et al, 2001;Hannas et al, 2000;Moreira et al, 2002. In this trial, the CCGG showed greater values of standard deviation for PUN than DLGG (Table 2).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…PUN generally shows a high variance (Coma et al, 1995) and in some studies, PUN was not efficient to determine the lysine requirement (Fontes et al,.1999;Gasparotto et al, 2001;Hannas et al, 2000;Moreira et al, 2002. In this trial, the CCGG showed greater values of standard deviation for PUN than DLGG (Table 2).…”
Section: Resultsmentioning
confidence: 74%
“…The PUN, the result of amino acid catabolism, indicates the capacity of utilization of intake nitrogen by the animal (Brown and Cline, 1974). It's used for amino acid requirement determinations (Coma et al, 1995). In this trial, the DLGG showed quadratic response of the PUN (P=0.05).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the concentration of 2.26 mg a-tocopherol/kg meat would be the maximum concentration obtained most efficiently. Broken-line regression analysis has been used satisfactorily to estimate the requirements of nutrients in some species such as lysine in pigs (Coma et al, 1995), isoleucine in pigs (Robbins et al, 2006) and vitamin E in fish (Shiau and Shiau, 2001;Lin and Shiau, 2005). The only reference found concerning the application of broken-line regression analysis to determine the optimum dietary supplementation of vitamin E in lambs was in Lopez Bote et al (2001).…”
Section: Fattening Periodmentioning
confidence: 99%
“…O mesmo comportamento foi obtido por COMA et al (1995), que, trabalhando com suínos de 32 a 36 kg de peso vivo, obtiveram efeito quadrático dos níveis de lisina sobre a concentração de NUP, com menor nível em 0,85% de lisina na ração, portanto inferior àquele estimado no presente experimento.…”
Section: = Coeficiente De Variação % (Cv = Coefficient Of Variatiunclassified